2007
DOI: 10.3748/wjg.v13.i37.5009
|View full text |Cite
|
Sign up to set email alerts
|

Liver angiogenesis as a risk factor for hepatocellular carcinoma development in hepatitis C virus cirrhotic patients

Abstract: AIM:To evaluate the predictive value of hepatocyte proliferation and hepatic angiogenesis for the occurrence of Hepatocellular carcinoma (HCC) in hepatitis C virus (HCV) cirrhotic patients. METHODS:One hundred-five patients (69 males, 36 females; age range, 51-90 year; median 66 year) with biopsy proven HCV cirrhosis were prospectively monitored for HCC occurrence for a median time of 64 mo. Angiogenesis was assessed by using microvessel density (MVD), hepatocyte turnover by MIB1 and PCNA indexes at inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
(18 reference statements)
0
5
0
2
Order By: Relevance
“…Indeed, high hepatic level of 8-hydroxy-2 0 -deoxyguanosine (marker of DNA damage induced by oxidative stress), as well as histologic markers of liver angiogenesis are associated with a higher incidence of HCC in patients with HCV cirrhosis (4,5). In liver, HCV proteins induce NADPH oxidase 4 expression and subsequent reactive oxygen species (ROS) production through an autocrine TGFb-dependent mechanism, trigger mitochondrion-derived ROS and angiogenesis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high hepatic level of 8-hydroxy-2 0 -deoxyguanosine (marker of DNA damage induced by oxidative stress), as well as histologic markers of liver angiogenesis are associated with a higher incidence of HCC in patients with HCV cirrhosis (4,5). In liver, HCV proteins induce NADPH oxidase 4 expression and subsequent reactive oxygen species (ROS) production through an autocrine TGFb-dependent mechanism, trigger mitochondrion-derived ROS and angiogenesis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HCV-positive sera and liver homogenates enhanced proliferation and migration of endothelial cells compared with controls and HBVpositive patients (Mazzanti et al, 1997). According to these data, it has been recently demonstrated that liver angiogenesis, estimated by the microvessel density in liver biopsies of patients affected by HCV-related liver cirrhosis, can be predictive of the occurrence of HCC (Mazzanti et al, 2007).…”
Section: Hcv Infectionmentioning
confidence: 93%
“…Low expression of MVD was for scores from 0 to 3. The ones with scores ≥ 4 were considered high MVD [29].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%